Murder by death [videorecording (Blu-Ray)] - Moore, Robert, 1927-1984; Simon, Neil; Stark, Ray; Guinness, Alec, 1914-2000; Falk, Peter, 1927-2011; Sellers, Peter, 1925-1980; Brennan, Eileen; Capote, Truman, 1924-1984; Coco, James; Lanchester, Elsa, 1902-1986; Niven, David, 1910-1983; Smith, Maggie, 1934-2024; et al. (Shout select., 2018)
An eccentric millionaire invites five world famous detectives to dinner and reveals to them that at midnight, someone in the dining room will be killed and the others must solve the crime.